Double-blinded, randomised, placebo-controlled trial of convalescent plasma for COVID-19: analyses by neutralising antibodies homologous to donors' variants - Khawaja, T. (Informa Healthcare, 2025)
Introduction
Convalescent plasma (CP) emerged as potential treatment for COVID-19 early in the pandemic. While efficacy in hospitalised patients has been lacklustre, CP may be beneficial at the first stages of disease. Despite multiple new variants emerging, no trials have involved analyses on variant-specific antibody titres of CP.
Methods
We recruited hospitalised COVID-19 patients within 10 days of symptom onset and, employing a double-blinded approach, randomised them to receive 200 ml convalescent plasma with high (HCP) or low (LCP) neutralising antibody (NAb) titre against the ancestral strain (Wuhan-like variant) or placebo in 1:1:1 ratio. Primary endpoints comprised intubation, corticosteroids for symptom aggravation, and safety assessed as serious adverse events. For a preplanned ad hoc analysis, the patients were regrouped by infused CP’s NAb titers to variants infecting the recipients i.e. by titres of homologous HCP (hHCP) or LCP (hLCP).
Results
Of the 57 patients, 18 received HCP, 19 LCP and 20 placebo, all groups smaller than planned. No significant differences were found for primary endpoints. In ad hoc analysis, hHCPrecipients needed significantly less respiratory support, and appeared to be given corticosteroids less frequently (1/14; 7.1%) than those receiving hLCP (9/23; 39.1%) or placebo (8/20; 40%), (p = 0.077).
Discussion
Our double-blinded, placebo-controlled CP therapy trial remained underpowered and does not allow any firm conclusions for early-stage hospitalised COVID-19 patients. Interestingly, however, regrouping by homologous – recipients’ variant-specific – CP titres suggested benefits for hHCP. We encourage similar re-analysis of ongoing/previous larger CP studies.